Public Perception of The Ease of Donating and The Effectiveness of Using Fintech in Paying Zakat and Alms on The Kitabisa Application: (Case Study Of Sumberbendo Village, Pare District) - Rahmawati, Indah; Puspita, Erna; Zaman, Badrus (Universitas Nusantara PGRI Kediri, 2023)
Research Aim : The following research aims to recognize the effect of public perception on the ease of donating and the effectiveness of using fintech in paying zakat and alms on Kitabisa.com applications. Research Method : This research uses quantitative methods with an associative approach. Sample collection uses the purposive sampling method with consideration of the community who have kitabisa.com application in Sumberbendo Village, Pare District. The total population was 5,415, while the sample that met the criteria was obtained by 225 speakers. Sampling is carried out by distributing questionnaires using google forms with statements that have been tested for validity and related reliability. In testing the hypothesis, use multiple linear regression testing through the SPSS application. Research Finding : The results of this research found that the perception of the ease and effectiveness of using fintech has a positive influence and has a significant impact on zakat and alms payment decisions with the Kitabisa application.